Hybrid Renewable Energy Power System Model Based on Electrification Requirements of One Fathom Bank Malaysia - S. Sarip; C. G. Abdullah; N. Shafie; N. A. N. Mahadzir; F. Yakob; M. Z. Hassan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Renewable energy resources are becoming inexorably in the field of generating electrical power due to the fast development of technology, given to its advantages over non-renewable energy resources. Though the source is available in enormous amount, energy produced from single renewable energy resources such as tidal current may fluctuate with the time and the hour of the day or month, depending on the tides. Thus, by having a hybrid power system consisting two or more renewable energy resources coming into play at the same time would be more reliable to support the targeted area. However, the availability of renewable energies depends on the climate change, therefore having a storage battery or backup power is often essential. In this case, the main purpose of this research is to develop an off-grid hybrid tidal current and solar power system along with backup power to support One Fathom Bank Lighthouse in Malaysia with the intention to reduce the dependency on diesel generators. Having the ability to evaluate economic and technical feasibility of power system, HOMER software is used to run simulation and analyze the best combination of components to form a hybrid power system for the lighthouse. The results are based on the best components and sizing in compliance with the load demand and diesel fuel consumption to provide a reliable and cost-effective system.